Diabetes- is patient knowledge the key to self-management - Fitzsimmons , Claire; Hollywood, Brid (Trinity Student Medical Journal, 2006)
Type 2 diabetes is a chronic metabolic disorder and community-based management poses many challenges to both healthcare professionals and patients. This article explores the attitudes of two different diabetic patients towards their condition by means of informal interviews. The relationship between patient knowledge and compliance with treatment regimes is also investigated through the two case studies. Current strategies for managing Type 2 diabetes in the primary-care setting are also reviewed.